The impact of urbanization on risk for eating disorders. Issue 3 (May 2019) - Gorrell, Sasha; Trainor, Claire; Le Grange, Daniel
Abstract : Purpose of review: Urbanization has broadly been implicated in negatively impacting mental health, including risk for disordered eating and eating disorders. Understanding the specific mechanisms that contribute to risk for maladaptive eating behavior in the context of urbanization is essential to improving public health policy and guiding future clinical, research, and prevention efforts. Recent findings: This review of recent investigation related to the impact of urbanization on eating disease highlights specific risk factors for eating disorders, including acculturation to Western standards of beauty and food resources with associated body weight and body image concern. Summary: Recommendations for clinical and research endeavors include improved specificity in defining urbanization, as well as increased sensitivity within community-based assessment of cultural and demographic variables that may impact eating behavior and risk for eating disorders.